Management of the Qur’an Memorization Program at Darussalam Islamic Boarding School in Sampit - Hikmah, Siti Fathonatul; Siminto; Riyadi, Slamet (Universitas Negeri Jakarta, 2025)
Background Managing a Qur’an memorization program for young students poses unique challenges, as it requires managerial strategies that are appropriate to their developmental stages and necessitates the involvement of multiple stakeholders, including parents. Purpose The purpose of this study is to analyze the management of the Qur’an memorization program at Darussalam Islamic Boarding School in Sampit, with a specific focus on the aspects of planning and implementation, as well as to identify the supporting factors and obstacles encountered. Design/method/approach This study employs a qualitative descriptive method, with data collected through observation, in-depth interviews, and document analysis. Results The results of the study indicate that the management of the Qur’an memorization program is carried out systematically through several stages: planning memorization targets, implementing activities tailored to the children's characteristics and needs, and conducting regular evaluations through tasmi’, munaqosah, and muroja’ah. The program’s success is supported by teachers’ commitment, a conducive boarding school environment, and effective motivational strategies. The main challenges include the lack of parental involvement and inconsistency in memorization during holidays or when the children are at home. Contribution/value To address these challenges, it is necessary to strengthen collaboration between the boarding school and parents, as well as to develop a more robust and consistent evaluation system. The findings of this study can serve as a reference for other Islamic educational institutions in designing adaptive and sustainable Qur’an memorization programs.